Design Of Triangular Array Microstrip Patch For Antenna 5g Application - Imelda Uli Vistalina Simanjuntak; Agus Dendi Rochendi; Ketty Siti Salamah; Diah Sucita Safitri (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
The trend of research on microstrip antennas in the millimeter frequency range has been hotly discussed in recent years. With the aim of increasing the bandwidth, beam gain and return loss in accordance with the standards of 5G needs in a fairly small dimension and low complexity. Previously, several studies of microstrip antennas with conventional patches have been carried out, then followed by a triangular array patch model. The antenna designed using Duroid 5880 substrate with a thickness of 1.575 mm and a dielectric constant value of 2.2 was simulated using Computer Simulation Technology (CST) software. The simulation results work at a frequency of 28 GHz with a return loss value of -26.98 dB, VSWR 1.09, gain 8.8 dB, HPBW value of 25.6° and main lobe of 21.0 dBi. This antenna can work well on millimeter wave range for 5G technology. Compared with previous studies of microstrip antennas, this triangular array patch antenna provides better measurement results.